IMPACT REPORTING THE RESULTS OF THE IMPLEMENTATION OF AUTOMATED EQUIPMENT ON THE COMPETITIVENESS OF COMPANIES: IMPACT REPORTING THE RESULTS OF THE IMPLEMENTATION OF AUTOMATED EQUIPMENT ON THE COMPETITIVENESS OF COMPANIES - Peeva, Svetla (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The present study aims to show the direct and indirect impact of process automation on the degree of competitiveness of a company. The subject of comparison are the approaches in the choice of a model of technological equipment and the social and economic efficiency. The relationship between benefits and risks in making such important for business development decisions is analyzed.